EBMT−NIH−CIBMTR Task Force position statement on standardized terminology & guidance for graft-versus-host disease assessment. (November 2018) - Schoemans, Helene; Lee, Stephanie; Ferrara, James; Wolff, Daniel; Levine, John; Schultz, Kirk; Shaw, Bronwen; Flowers, Mary; Ruutu, Tapani; Greinix, Hildegard; Holler, Ernst; Basak, Grzegorz; et al.
Abstract Several international recommendations address the assessment of graft-versus-host disease (GvHD) after hematopoietic cell transplantation (HCT). This position statement by GvHD experts from the European Society for Blood and Marrow Transplantation (EBMT), the National Institutes of Health (NIH) and the Center for International Blood and Marrow Transplant Research (CIBMTR) reviews the existing guidelines for both acute and chronic GvHD, addresses potential confusions that arise in daily practice and proposes consensus definitions for many key terms. We provide a historical perspective on the currently available guidelines and recommend the Mount Sinai Acute GvHD International Consortium (MAGIC) criteria for acute GvHD and the NIH 2014 criteria for chronic GvHD as the most comprehensive and detailed criteria available. This statement also offers practical guidance for the implementation of these recommendations and a set of consensus definitions for commonly used GvHD terms in order to facilitate future clinical and translational research. To assist the dissemination of these recommendations, a web-application based on this position statement is available (https://www.uzleuven.be/egvhd ). We believe that adherence to a common set of GvHD assessment criteria is vitally important to improve the quality of data, compare results of retrospective studies and prospective clinical trials, and make therapeutic recommendations based on quality evidence.